Slang Words in Me, and Earl, and The Dying Girl Novel: Type and Interpretation - Sukma Septian Nasution; Lestari Juniarti Karimah; Setiana Sri Wahyuni Sitepu; Tryana Tryana; Laksmy Ady Kusumoriny (Makassar State University, 2021)
Abstract. As a written representation of society, novel contains sociolinguistic issues which deserve a comprehensive analysis one of which is the use of slang words. This study explored slang words used in Me and Earl and the Dying Girl, a novel written by Jesse Andrews. The aims of this study were to categorize types of slang words used in the novel and to explain the interpretations of them. The data were collected from the dialogues in the novel. Using qualitative approach, the writer used the theory of Chapman (1988) to classify the data into their types. To explain the interpretations of slang words, the writer analyzed the role relationship among the speakers, the way the actors speak, and the meaning of each slang word found using slang dictionaries. The analysis reveals that as the relationship among the actors are equal and they naturally raise within the community, actors in the novel dominantly use primary slang words. Conversation using secondary slang words take place when the actors are not engaged within the community.Keywords: Novel, Slang Words, Sociolinguistics